Le dromadaire en Algérie - Ben Aissa R. (Séminaire sur la digestion, la nutrition et l'alimentation du dromadaire, 1989)
This communication gives a progress report on the situation of the dromedary in Algeria starting from a library search and effective participation of stockbreeders and owners of dromedaries at the time of two national seminars.
Séminaire sur la Digestion, la Nutrition et l'Alimentation du Dromadaire, 1988/02/27-1988/03/01, Ouargla (Algeria)